Exploring the Effect of Long Naps on Handball Performance and Heart Rate Variability - Nishida, Masaki; Yamamoto, Kei; Murata, Yusuke; Ichinose, Atsushi; Shioda, Kohei (Sports Medicine International Open, 2021)
This study explored the effect of long naps on handball-related performance and assessed the role of the cardiac autonomic nervous system in this process. Eleven male collegiate handball players performed a repeated sequential trial consisting of a 20-m consecutive turnaround run, 10-m run with a load, and shooting the ball into a target. Participants were allocated randomly and sequentially to have a short (20 minutes) nap, long (60 minutes) nap, or no nap. The Pittsburgh Sleep Quality Index was used to assess regular sleep quality. Subjective sleepiness before and after napping was measured using the Karolinska Sleepiness Scale. Heart rate variability was recorded to assess cardiac autonomic nervous function during napping. The Pittsburgh Sleep Quality Index score was correlated with shot accuracy only after long naps (ρ=0.636, r=0.048). A negative correlation was observed between the root mean square of successive differences and average load run time (ρ=−0.929, p<0.001). Long napping was associated with a significant benefit on performance in athletes with poor sleep quality, implying a role of the autonomic nervous system in this regard. Our findings indicate the effect of sleep quality on the endurance and resistance of handball players.
Keywords: Nap; Sleep; Sports; Handball; Heart rate variability; Autonomic nervous system